Evaluation of the efficacy, safety, and satisfaction rate of topical latanoprost in patients with hypopigmented burn scars treated with fractional CO2 laser: a double-blind randomized controlled clinical trial - Atefi, Najmolsadat; Yeganeh, Zahra Parsaei; Bazargan, Afsaneh Sadeghzadeh; Yeganeh, Mohamad Saleh Parsaei; Jafarzadeh, Alireza; Zare, Mahin; Goodarzi, Azadeh (Lasers in medical science, 2025)
Burn scars present psychological and social challenges for patients, classified into atrophic and hypertrophic types. Treatments like corticosteroid injections, laser therapy, and platelet-rich plasma (PRP) injections are commonly recommended for hypertrophic scars, while regenerative medicine and fractional CO2 lasers are linked to some degree of improvement for atrophic scars. Hypopigmented and depigmented burn scars pose ongoing challenges for healthcare providers and patients, with therapies such as intense pulsed light and fractional CO2 laser showing variable effects in treating these conditions. This study evaluates the effectiveness of latanoprost, a prostaglandin analog, in combination with fractional CO2 laser for repigmentation of hypopigmented burn scar lesions. During the study, patients were treated with 0.005% latanoprost eye drop or normal saline twice a day for 6 months and underwent six monthly fractional CO2 laser sessions. Treatment instructions were provided by the physician, and patients were instructed to report any complications and avoid using other medications in the treatment area. Assessments included photography at the start of the study and in three follow-up sessions at three-month intervals. Improvement was assessed using the Subject Global Aesthetic Improvement Scale (SGAIS) by both the physician and patients. Patient satisfaction was evaluated using a Grade scale, and side effects were monitored in all follow-up sessions. In the third follow-up session, physicians assessing the Subject Global Aesthetic Improvement Scale (SGAIS) observed that a higher proportion (85.7%) of cases in the fractional CO2 laser with latanoprost group achieved a grade of 4 (50–74% improvement). In the placebo group, 0% of patients achieved grade 4, and 71.4% were classified as grade 2 (0–24% improvement), indicating a significant difference (P-value: 0.0001). Patient satisfaction, measured by the "Grade scale to evaluate patient satisfaction" index, revealed a notable contrast between the two groups, with average satisfaction scores of 8.50 ± 0.65 and 4.64 ± 1.00 for the fractional CO2 laser with latanoprost and placebo groups, respectively, indicating a statistically significant difference (P = 0.0001). Furthermore, throughout the study, no severe side effects were reported by any of the patients. Prostaglandin analogs, particularly latanoprost, have proven to be effective in promoting repigmentation of hypopigmented and depigmented burn scar lesions. When this topical medication is combined with fractional CO2 laser treatment, it enhances the laser's efficacy and overall effectiveness in treating the lesions. This combination is crucial for improving hypopigmented scar treatment by enhancing both the laser's effectiveness in scar improvement and the delivery of latanoprost through the laser. What is already known about this topic? Hypopigmented burn scars are one of the manifestations of burns that are resistant to treatment. These scars not only cause discomfort for patients but also present a treatment challenge for physicians. In previous studies, latanoprost and bimatoprost, analogs of prostaglandin PGF2a, showed effectiveness in repigmenting vitiligo lesions. However, no study has examined the role of these topical drugs in treating hypopigmented and depigmented burn scars. What does this study add? The fractional CO2 laser caused significant repigmentation in hypopigmented lesions of burn scars. 64.3% of the patients who received this intervention showed grade 2 improvement (0-24% improvement), 7.1% showed grade 3 improvement (25-49% improvement), and 28.6% showed no improvement (grade 1) in the third follow-up session based on the SGAIS criteria as evaluated by the patients. The combination of CO2 fractional laser and latanoprost caused significant repigmentation in hypopigmented burn scar lesions. 85.7% of patients showed grade 4 improvement (50-74% improvement), and 14.3% showed grade 3 improvement (25-49% improvement) and 0% showed no improvement (grade 1) in the third follow-up session based on the SGAIS criteria as evaluated by the patients. The combination of CO2 fractional laser and latanoprost was significantly more effective than CO2 fractional laser alone based on the SGAIS criteria, as evaluated by physicians and patients in all three follow-up sessions. Additionally, the satisfaction of the patients in the combined treatment group was significantly higher than that of the CO2 fractional laser treatment group.